Knowledge, attitude, and practice of underfive children stimulation of working and nonworking mothers - Trie Hariweni; Muhammad Ali; Sri Sofyani; Iskandar Z Lubis (Indonesian Pediatric Society, 2004)
Objective To assess and compare knowledge, attitude, and prac-tice of underfive children stimulation of working and nonworkingmothers and to determine the correlation between knowledge, at-titude, practice of stimulation and mothers’ ages, educational level,number of children, and number of underfive children.Methods A cross-sectional study was performed in PT. IndofoodSukses Makmur, Tanjung Morawa, Medan from October 2002 un-til November 2002. Respondents were female workers havingunderfive children assigned as working mothers and wives of maleworkers (with similar inclusion criteria) assigned as nonworkingmothers. Selected respondents were interviewed using a struc-tured questionnaire. Sample size for each group was 58. Knowl-edge, attitude, and practice of stimulation were classified as good,less, and poor.Results There were 131 mothers interviewed. There were no sig-nificant differences in the ages, educational level, number of chil-dren, and number of underfive children. Good knowledge of stimu-lation of the working and nonworking mothers were 64.6% and97%, respectively; good attitude toward stimulation were 95.4%and 27.3%, respectively, while good practice of stimulation were58.5% and 22.7%, respectively. These differences were statisti-cally significant.Conclusion There were significant differences in knowledge, atti-tude, and practice of underfive children stimulation between work-ing and nonworking mothers. The knowledge of stimulation of theworking mothers was worse than that of the nonworking mothersand the attitude and practice of the working mothers were betterthan those of the nonworking mothers